An Inclusive Early Childhood Intervention Program for Children With Disabilities: Possible Effects on Children and Nursery Teachers - Ueda, Kimiko; Goto, Aya; Imamoto, Toshikazu; Yamazaki, Yoshihisa (Frontiers in Rehabilitation Sciences, 2021)
Inclusive early childhood intervention provides opportunities for children with disabilities to receive education with typically developing children. The present study examined the effects of the AI-AI STEP Program, which is designed to help nursery teachers learn the methods of inclusive early childhood intervention for children with disabilities. This study involved 37 managers of 37 nursery schools in Japan, 48 nursery teachers, and 48 children with disabilities. The school managers, who had previously learned about the program through a seminar we offered, provided the nursery teachers with guidance on the program. The guidance provided to the nursery teachers consisted of combined structured explanations with a manual and on-the-job training. The program was performed for 6 months, and changes in the children’s development and behavior and the school nursery teachers’ self-efficacy and state-trait anxiety, were examined before and after using the program. Multivariate analysis was used to assess factors that had an effect on the children’s developmental gains through the program. The developmental quotient of children significantly improved. In addition, “emotional symptoms” and “peer problems” on the Strengths and Difficulties Questionnaire subscale markedly improved. The self-efficacy of nursery teachers significantly improved, and state anxiety decreased. There was a significant relationship between the improvement of the children’s development quotient and a lower development quotient at baseline. The provision of inclusive early childhood intervention using the program promoted the children’s development, and improved their behavior. Furthermore, it had a positive effect on the nursery teachers.